Changes in Sepsis Biomarkers after Immunosuppressant Administration in Transplant Patients - Janka Franeková; Marek Protuš; Eva Kieslichová; Aleš Březina; Jitka Komrsková; Jiří Vymětalík; Antonín Jabor (Mediators of Inflammation)
Sepsis biomarkers change continuously during the postoperative period. We aimed to demonstrate the influence of immunosuppressants after transplantation (Tx) on presepsin, procalcitonin, CRP, white blood cells, and IL-6. A group of 140 patients after major surgery (86 non-Tx, 54 Tx) without any signs of sepsis or infectious complications was followed for 7 days. The changes in biomarkers were analyzed with respect to the type of surgery, organ, and induction immunosuppressant used (antithymocyte globulin, corticosteroids, or basiliximab/rituximab). Concentrations (95th percentiles) of presepsin and procalcitonin were higher in the Tx group (presepsin: Tx<2380 vs. non‐Tx<1368 ng/L, p<0.05; procalcitonin: <28.0 vs. 3.49 μg/L, p<0.05). In contrast, CRP and IL-6 were lower in the Tx group (CRP: Tx<84.2 vs. non‐Tx<229 mg/L, p<0.05; IL-6: <71.2 vs. 317 ng/L, p<0.05). Decreases in CRP and IL-6 were found for all immunosuppressants, and procalcitonin was increased after antithymocyte globulin and corticosteroids. Negligible changes were found for white blood cells. Different responses of presepsin, procalcitonin, CRP, and IL-6 were therefore found in patients without any infectious complications after major surgery or transplantation. Immunosuppression decreased significantly IL-6 and CRP in comparison to non-Tx patients, while procalcitonin was increased after corticosteroids and antithymocyte globulin only. Cautious interpretation of sepsis biomarkers is needed in the early posttransplant period. This work was conducted as a noninterventional (nonregistered) study.